TINJAUAN TENTANG KESESUAIAN ISI BUKU TEKS KIMIA SMA KELAS X PADA POKOK BAHASAN STRUKTUR ATOM DAN SISTEM PERIODIK UNSUR DENGAN KURIKULUM 2013 - Lusi Febrika; R. Usman Rery; Islamias Islamias (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstrack: This study aims to determine the suitability of the content of high schoolchemistry textbooks class X with feasibility contents and feasibility presentation on thesubject of atomic structure and the periodic system unsure with Curriculum 2013. Thisresearch was conducted at PMIPA Chemistry Study Program Guidance and CounselingUniversity of Riau. Data retrieval time is in April 2014 through June 2014. Populationof this study is high school chemistry textbooks which is the subject of class X of atomicstructure and the periodic system unsure labeled Curriculum 2013. Data was collectedby observation techniques dominant book. Data analysis by using descriptive analysis.Based on the research that has been conducted found that the major conclusions ofconformity feasibility Erlangga chemistry textbook content was 72.22% and Yudhistira70.22% were the suitability category "Enough". Suitability of large chemical textbookspresenting feasibility Erlangga are 89.13% and Yudhistira 87.56% is conformity withthe category of "Good". Based on the percentage of Erlangga chemistry textbooks havesuitability levels higher than Yudhistira chemistry textbooks. Percentage obtained byErlangga chemistry textbooks and Yudhistira chemistry textbooks used according to thelabel on the outside of the textbookKeywords: curriculum 2013, textbook